(untitled) (Research, Society and Development, 2020)
The objective of this work was to verify the sodium and sugar content of products intended for children by means of nutrition labeling. This is a cross-sectional study, exploratory, descriptive and quantitative, in which 101 samples of labeling from 56 different food brands were collected. The information was collected through the photographic record and the analyzed products were categorized into 9 food groups. For the analysis of the levels of sodium and sugar, a standard portion of 100g / 100ml of each product was established and these were categorized according to the concentration range, as well as were also compared with the intake recommendations established by the Dietary Reference Intakes (DRI) and World Health Organization (WHO). Most of the products had sugar contents in the range of 0 to 15 g/100 g, with emphasis on salty snacks, snacks and soups and in the range of 0 to 300 mg/100 g of sodium, highlighting food supplements and soups. The group of dairy products (78.41%), sweets (71.14%) and breakfast cereals (68.99%) obtained the highest percentages of adequacy for sugar, whereas for sodium they were the group of soups (197.2%), sausages (97.6%) and snacks and (57.6%). It was concluded that the analyzed products presented significant levels of sugar and sodium according to the nutrition labeling, as well as a high percentage of adequacy when compared to the daily recommendations of said nutrients in the DRI and WHO.